2014
DOI: 10.5506/aphyspolb.45.1771
|View full text |Cite
|
Sign up to set email alerts
|

Transition Network Entropy in Characterization of Complexity of Heart Rhythm After Heart Transplantation

Abstract: The transition network for RR-increments is a directed and weighted graph, where the vertices represent RR-increments and the edges correspond to subsequent increments. We show that based on the transition matrix of this network, the entropy of heart rhythm can be calculated. We compare the entropy of the distributions of eigenvalues of the transition matrix for heart transplant patients and for healthy young subjects. We show the regulatory effect of the autonomic nervous system on the entropy values and eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…The transition matrix of this network leads to the Markov characterization of the dynamics, and hence, it provides the entropy rate as an estimator of the total complexity of the time series. This approach is a continuation of our earlier investigations into the usability of network theory tools in the assessment of RR-time interval signals [8]. Our second method is based on the distribution of ordinal patterns and the resulting permutation entropy [1,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The transition matrix of this network leads to the Markov characterization of the dynamics, and hence, it provides the entropy rate as an estimator of the total complexity of the time series. This approach is a continuation of our earlier investigations into the usability of network theory tools in the assessment of RR-time interval signals [8]. Our second method is based on the distribution of ordinal patterns and the resulting permutation entropy [1,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Our concept of fragmentation includes zero value RR-increments. This extension is important because in the case of heart rhythms of HTX patients, we observe an abundance of zero RR-increments (Makowiec et al, 2013 , 2014 ).…”
Section: Introductionmentioning
confidence: 84%
“…By observing subsequent changes in RR-intervals, we obtain beat-to-beat information about the resulting force of these interactions. We have found that important dynamical aspects about the autonomic competitive regulation can be described by changes in RR-intervals, namely by RRincrements ( [20], [21]).…”
Section: Introductionmentioning
confidence: 98%